Responses of protist communities to spatio-temporal changes in water masses in the northeastern East China Sea in 2023 - Hye Jin Seo; Hyun Jun Yang; Yun Hee Kim; Dohyeop Yoo; Hyebin Kim; Jiae Yoo; Sunju Kim; Yoonja Kang; Tae-Hoon Kim; Byoung-Ju Choi; Adrian Marchetti; Se Hyeon Jang (Algae, 2026)
This study explores the dynamics of protist communities in the northeastern East China Sea (ECS) focusing on their responses to changing water masses and oceanographic conditions during spring, summer, and autumn in 2023. Water masses were classified using K-means clustering based on physico-chemical parameters, revealing significant seasonal variation. Protist community spatial, temporal, and vertical distributions were analyzed using 18S rRNA gene amplicon sequencing and morphological identification along the 33° N latitude, a region characterized by the confluence of multiple water masses, including Kuroshio surface (KSW) and sub-surface (KSSW) waters, Yellow Sea water (YSW), Changjiang diluted water (CDW), and ECS Shelf water. Protist diversity, community structure, and cell abundance exhibited pronounced seasonal variations influenced by temperature, salinity, and nutrient availability. In spring, YSW, characterized by phosphate deficiencies and, consequently, increased N : P ratios, exhibited a prevalence of dinoflagellates, whose phagotrophic capabilities likely conferred a competitive advantage in such nutrientfluctuating environments. During summer, diatoms were prevalent in the ECS Shelf water, underscoring the role this water plays in shaping seasonal community structure. In contrast, CDW exhibited low species diversities, likely due to unstable salinity. In autumn, water column mixing increased overall diversity and cell abundance, particularly in YSW, where Chaetoceros socialis and other diatoms thrived. Potential phosphorus limitation, especially in the western waters, may have further influenced the spatial structuring of communities across seasons. These findings highlight complex interactions between oceanographic factors and protistan communities in the northeastern ECS, contributing to a deeper understanding of their distributions and responses to environmental changes.

Hyperspectral optical signatures of iron‐limitation in a coastal upwelling system - Sacchidanandan V. Pillai; Yayla Sezginer; Adrian Marchetti; Claire P. Till; Emily V. Speciale; Philippe D. Tortell (Limnology and Oceanography, 2026)
Iron‐limitation within the California Current System drives changes in phytoplankton taxonomic composition and photo‐physiology over a range of spatial scales. Here we demonstrate how these iron‐dependent signatures can be resolved, with high spatial resolution, using continuous ship‐board optical measurements. Deck‐board incubation experiments, along with discrete measurements of iron and macro nutrient concentrations and molecular diagnostic signatures, demonstrated contrasting levels of iron stress across our study region in the northern California Current System during summer, 2023. Photosynthetic pigment measurements indicated that phytoplankton assemblages were largely dominated by diatoms, but low and high iron waters contained differing relative abundances of phytoplankton genera with different mean cell sizes. High frequency ship‐board measurements of hyperspectral particulate absorption demonstrated the presence of two optically distinct phytoplankton assemblages that were associated with varying levels of iron stress. The distribution of the optical clusters across the cruise track showed strong coherence with a number of oceanographic and physiological variables, including phytoplankton size, nutrient drawdown ratios, photosynthetic efficiency () and absorption cross‐section (), and maximum photosynthetic rates. Notably, optical signatures explained more of the observed photo‐physiological variability than other oceanographic variables, such as sea surface temperature and chlorophyll concentration. Variability in phytoplankton iron stress appeared coupled to the age and source of the upwelling water masses. Our results demonstrate the utility of hyperspectral data to map potential iron‐stress with high spatial resolution in dynamic coastal waters.

Drivers of Marine Phytoplankton Diversity and Connectivity in the Galápagos Archipelago Spanning an ENSO Cycle - Prisca Lim; Harvey Seim; Oliva Torano; Erika Neave; Se Hyeon Jang; Zackary Johnson; Sara Haines; Scott Gifford; Natalie Cohen; Carly M. Moreno; Margarita Lankford; Cristina Vintimilla Palacios; et al. (Environmental Microbiology, 2025)
The Galápagos Islands are a biodiversity hotspot, largely due to the Equatorial Undercurrent (EUC) which supplies nutrient‐rich waters to the euphotic zone and supports enhanced levels of primary productivity performed by phytoplankton. Understanding phytoplankton responses to changing environmental conditions is crucial for regional conservation and management efforts. Research cruises conducted between 2014 and 2022, spanning a major El Niño event in 2015 and a La Niña event in 2022, observed varying oceanic conditions and diverse phytoplankton community composition. At most EUC‐influenced stations, larger‐sized phytoplankton groups (≥ 5 μm) were dominant while warmer, oligotrophic sites favoured smaller‐sized phytoplankton groups (

Phytoplankton Exhibit Diverse Responses to Different Phases of Upwelling in the California Current System - Yuan Yu Lin; Olivia Torano; Emily Pierce; Claire Till; Matthew Hurst; Astrid Schnetzer; Harvey Seim; Adrian Marchetti (Environmental Microbiology, 2025)
Eastern boundary upwelling currents are some of the most biologically productive and diverse regions in the world's oceans. Driven by equatorward winds and Ekman transport, surface waters are transported offshore and replaced by cold, nutrient‐rich deep waters that seed extensive phytoplankton blooms. Studying phytoplankton community succession and physiological acclimation during the initial stages of upwelling is critical to building a comprehensive understanding of phytoplankton responses to upwelling in these important regions. Additionally, factors like lateral transport, seed population dynamics and physiological and molecular shifts are conducive to shaping the community assemblage and primary productivity. This study examines how phytoplankton gene expression and resulting physiology change between early and later phases of upwelling. By incorporating metatranscriptomic analyses and stable isotope incubations to measure nutrient uptake kinetics into our assessment of early and later upwelling stages, we observed variability in phytoplankton assemblages and differential gene expression of phytoplankton that were de‐coupled from their physiology. We show that the gene expression response to a fresh upwelling event precedes their physiological response. Ultimately, understanding how phytoplankton change through the course of an upwelling event is critical to assessing their importance to regional biological rate processes, trophic systems and resulting biogeochemistry.

Corrigendum: Diatom transcriptional and physiological responses to changes in iron bioavailability across ocean provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2025)

Microbial respiration in contrasting ocean provinces via high-frequency optode assays - Melanie R. Cohn; Brandon M. Stephens; Meredith G. Meyer; Garrett Sharpe; Alexandria K. Niebergall; Jason R. Graff; Nicolas Cassar; Adrian Marchetti; Craig A. Carlson; Scott M. Gifford (Frontiers in Marine Science, 2024)
Microbial respiration is a critical component of the marine carbon cycle, determining the proportion of fixed carbon that is subject to remineralization as opposed to being available for export to the ocean depths. Despite its importance, methodological constraints have led to an inadequate understanding of this process, especially in low-activity oligotrophic and mesopelagic regions. Here, we quantify respiration rates as low as 0.2 µ mol O 2 L -1 d -1 in contrasting ocean productivity provinces using oxygen optode sensors to identify size-fractionated respiration trends. In the low productivity region of the North Pacific Ocean at Station Papa, surface whole water microbial respiration was relatively stable at 1.2 µ mol O 2 L -1 d -1 . Below the surface, there was a decoupling between respiration and bacterial production that coincided with increased phytodetritus and small phytoplankton. Size-fractionated analysis revealed that cells <5 µ m were responsible for the majority of the respiration in the Pacific, both at the surface and below the mixed layer. At the North Atlantic Porcupine Abyssal Plain, surface whole water microbial respiration was higher (1.7 µ mol O 2 L -1 d -1 ) than in the Pacific and decreased by 3-fold below the euphotic zone. The Atlantic size-fraction contributions to total respiration shifted on the order of days during the evolution of a phytoplankton bloom with regular storm disturbances. The high-resolution optode method used in the Atlantic captured these significant shifts and is consistent with coinciding stain-based respiration methods and historical site estimates. This study highlights the dynamic nature of respiration across vertical, temporal, and size-fractionated factors, emphasizing the need for sensitive, high-throughput techniques to better understand ocean ecosystem metabolism.

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

The Dawn of the BioGeoSCAPES Program: Ocean Metabolism and Nutrient Cycles on a Changing Planet - Mak Saito; Harriet Alexander; Heather Benway; Philip Boyd; Martha Gledhill; Elizabeth Kujawinski; Naomi Levine; Mairead Maheigan; Adrian Marchetti; Ingrid Obernosterer; Alyson Santoro; Dalin Shi; et al. (Oceanography, 2024)
Biogeochemical cycles constitute Earth’s life support system and distinguish our planet from others in this solar system. Microorganisms are the primary drivers of these cycles. Understanding the controls on marine microbial dynamics and how microbes will respond to environmental change is essential for building and assessing model-based forecasts and generating robust projections of climate change impacts on ocean productivity and biogeochemical cycles. An international community effort has been underway to create a global-scale marine microbial biogeochemistry research program to tackle gaps in this understanding. The BioGeoSCAPES: Ocean Metabolism and Nutrient Cycles on a Changing Planet program will identify and quantify how marine microbes adjust to a changing climate and assess the consequences for global biogeochemical cycles. This article summarizes the ongoing efforts to launch BioGeoSCAPES.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Protistan Communities Within the Galápagos Archipelago With an Emphasis on Micrograzers - Se Hyeon Jang; Prisca Lim; Olivia Torano; Erika F. Neave; Harvey Seim; Adrian Marchetti (Frontiers in Marine Science, 2022)
The Galápagos Archipelago is a globally significant biodiversity hotspot. However, compared to the relatively well-known megafauna, the distribution and ecological significance of marine protists in this system are poorly understood. To gain an understanding of the protistan assemblages across trophic modes, an intensive oceanographic survey was conducted in the Galápagos Marine Reserve (GMR) in October of 2018. The Equatorial Undercurrent (EUC)-influenced region had higher chlorophyll- a (Chl- a ) concentrations than those of the eastern regions of the archipelago, along with higher abundances of protistan grazers. Specifically, proportions of autotrophic and potentially mixotrophic dinoflagellates were higher in the EUC, whereas in the eastern regions, heterotrophic dinoflagellates and chlorophytes dominated. Taxonomic composition and biochemical indicators suggested proportions of micrograzers and their associated heterotrophic biomass was higher in the oligotrophic, low Chl- a regions in the east. We also report observations from a dinoflagellate bloom in the western archipelago, which was heavily influenced by upwelling of the EUC. The red tide-forming dinoflagellate Scrippsiella lachrymosa was highly detected through light microscopy and DNA amplicon sequencing. In addition, the heterotrophic dinoflagellate Polykrikos kofoidii was detected and, based on cell densities observed in this study and grazing rates obtained from the literature, estimated to potentially graze up to 62% of S. lachrymosa bloom population. Our findings thus provide new insights into the composition of micrograzers and their potential roles in structuring protistan communities in the Galápagos Archipelago.

Protistan plankton communities in the Galápagos Archipelago respond to changes in deep water masses resulting from the 2015/16 El Niño - Erika F. Neave; Harvey Seim; Scott M. Gifford; Olivia Torano; Zackary I. Johnson; Diego Páez‐Rosas; Adrian Marchetti (Environmental Microbiology, 2022)
Summary The Galápagos Archipelago lies within the Eastern Equatorial Pacific Ocean at the convergence of major ocean currents that are subject to changes in circulation. The nutrient‐rich Equatorial Undercurrent upwells from the west onto the Galápagos platform, stimulating primary production, but this source of deep water weakens during El Niño events. Based on measurements from repeat cruises, the 2015/16 El Niño was associated with declines in phytoplankton biomass at most sites throughout the archipelago and reduced utilization of nitrate, particularly in large‐sized phytoplankton in the western region. Protistan assemblages were identified by sequencing the V4 region of the 18S rRNA gene. Dinoflagellates, chlorophytes and diatoms dominated most sites. Shifts in dinoflagellate communities were most apparent between the years; parasitic dinoflagellates, Syndiniales , were highly detected during the El Niño (2015) while the dinoflagellate genus, Gyrodinium , increased at many sites during the neutral period (2016). Variations in protistan communities were most strongly correlated with changes in subthermocline water density. These findings indicate that marine protistan communities in this region are regimented by deep water mass sources and thus could be profoundly affected by altered ocean circulation.

Low diversity of a key phytoplankton group along the West Antarctic Peninsula - Michael S. Brown; Jeff S. Bowman; Yajuan Lin; Colette J. Feehan; Carly M. Moreno; Nicolas Cassar; Adrian Marchetti; Oscar M. Schofield (Limnology and Oceanography, 2021)
The West Antarctic Peninsula (henceforth “Peninsula”) is experiencing rapid warming and melting that is impacting the regional marine food web. The primary phytoplankton groups along the Peninsula are diatoms and cryptophytes. Relative to diatoms, there has been little focus on regional cryptophytes, and thus our understanding of their diversity and ecology is limited, especially at the species level. This gap is important, as diatoms and cryptophytes play distinct roles in the regional marine food web and biogeochemistry. Here, we use a phylogenetic placement approach with 18S rRNA gene amplicon sequence variants to assess surface ocean cryptophyte diversity and its drivers at a high taxonomic resolution along the Peninsula. Data were collected over 5 years (2012–2016) during the regional research cruises of the Palmer Long‐Term Ecological Research program. Our results indicate that there are two major cryptophyte taxa along the Peninsula, consisting of distinct Geminigera spp., which in aggregate always comprise nearly 100% of the cryptophyte community (indicating low taxa evenness). The primary taxon dominates the cryptophyte community across all samples/years, which span a broad range of oceanographic conditions. A shift in cryptophyte community composition between a lower (higher) primary (secondary) taxon percentage is associated with distinct oceanographic conditions, including lower (higher) temperature, salinity, nutrients, and cryptophyte relative abundance (phytoplankton biomass and diatom relative abundance). These results emphasize the need for a full characterization of the ecology of these two taxa, as it is predicted that cryptophytes will increase along the Peninsula given projections of continued regional environmental change.

Efficient zinc/cobalt inter‐replacement in northeast Pacific diatoms and relationship to high surface dissolved Co : Zn ratios - Riss M. Kellogg; Matthew R. McIlvin; Jagruti Vedamati; Benjamin S. Twining; James W. Moffett; Adrian Marchetti; Dawn M. Moran; Mak A. Saito (Limnology and Oceanography, 2020)
The importance of zinc (Zn) as a nutrient and its ability to be substituted for by cobalt (Co) have been characterized in model marine diatoms. However, the extent to which this substitution capability is distributed among diatom taxa is unknown. Zn/Co metabolic substitution was assayed in four diatom species as measured by the effect of free ion concentrations of Zn 2+ and Co 2+ on specific growth rate. Analysis of growth responses found substitution of these metals can occur within the northwest Atlantic isolate Thalassiosira pseudonana CCMP1335, the northeast Atlantic isolate Phaeodactylum tricornutum CCMP632, and within the northeast Pacific isolates Pseudo‐nitzschia delicatissima UNC1205 and Thalassiosira sp. UNC1203. Metabolic substitution of Co in place of Zn in the Atlantic diatoms supports their growth in media lacking added Zn, but at the cost of reduced growth rates. In contrast, highly efficient Zn/Co substitution that supported growth even in media lacking added Zn was observed in the northeast Pacific diatoms. We also present new data from the northeast Pacific Line P transect that revealed dissolved Co and Zn ratios (dCo : dZn) as high as 3.52 : 1 at surface (0–100 m) depths. We posit that the enhanced ability of the NE Pacific diatoms to grow using Co is an adaptation to these high surface dCo : dZn ratios. Particulate metal data and single‐cell metal quotas also suggest a high Zn demand in diatoms that may be partially compensated for by Co.

Phytoplankton composition in a eutrophic estuary: Comparison of multiple taxonomic approaches and influence of environmental factors - Weida Gong; Nathan Hall; Hans Paerl; Adrian Marchetti (Environmental Microbiology, 2020)
Summary To assess the comparability between taxonomic identification methods for phytoplankton, multiple approaches were used to characterize phytoplankton community composition within the Neuse River Estuary (NRE), North Carolina. Small subunit 18S rRNA gene sequencing and accessory pigment analysis displayed similar trends, indicating chlorophytes were the dominant microalgal group during most of the year, whereas results from microscopic cell counts, biovolume analysis and metatranscriptomics suggested diatom and dinoflagellate‐dominated communities. Spatial environmental gradients drove variation in taxonomic composition due to preferences for specific environmental conditions among different microalgal groups. Cryptophytes were a greater proportion of the phytoplankton community within high nutrient, fresher environments whereas diatoms and dinoflagellates dominated higher salinity sections of the estuary. This study provides a detailed examination of phytoplankton communities associated with environmental gradients present in the NRE. The high level of taxonomic resolution offered by DNA sequencing (i.e., species to sub‐species level) provides a better understanding of population dynamics at the base of estuarine food webs.

Interactive effects of iron and light limitation on the molecular physiology of the Southern Ocean diatom Fragilariopsis kerguelensis - Carly M. Moreno; Weida Gong; Natalie R. Cohen; Kimberly DeLong; Adrian Marchetti (Limnology and Oceanography, 2020)
The polar diatom Fragilariopsis kerguelensis is ubiquitous in Southern Ocean waters and is a major responder to iron fertilization, encountering large gradients in iron concentrations and light availability. We performed a comparative transcriptomic analysis of F. kerguelensis grown under varying iron and light conditions in order to investigate the molecular underpinnings that may explain its physiological response to iron and light limitation. Low iron reduced growth rates more than low light, but there was not an additive effect of low iron and low light on growth rate. Low iron treatments (saturating and low light) had the largest transcriptomic response; however, expression patterns were more similar in low light treatments (high and low iron). Under iron and light limitation, carbon fixation and amino acid, ribosome, and sulfur metabolisms were overrepresented relative to the control (iron replete, saturating light). Transcripts of genes encoding for the proteins aquaporin, proteorhodopsin, plastocyanin, and flavodoxin were overrepresented to the greatest extent in the low iron/low light treatment, indicating there may be an additive effect of iron/light colimitation at the molecular level. Iron and light replete cells demonstrated increased expression of genes encoding for the proteins ferritin, carbonic anhydrase, and numerous iron‐dependent proteins relative to the growth‐limiting treatments. This transcriptome analysis reveals mechanisms that may underpin the ecological success of this diatom in low iron and light environments, highlighting the important role of diversified photosynthetic isoforms, iron acquisition, unique detoxification mechanisms of reactive oxygen species, and metabolic shifts in amino acid recycling and carbon metabolism.

Estimation of 18S Gene Copy Number in Marine Eukaryotic Plankton Using a Next-Generation Sequencing Approach - Weida Gong; Adrian Marchetti (Frontiers in Marine Science, 2019)

Transcriptomic and proteomic responses of the oceanic diatom Pseudo‐nitzschia granii to iron limitation - Natalie R Cohen; Weida Gong; Dawn M. Moran; Matthew R. McIlvin; Mak A. Saito; Adrian Marchetti (Environmental Microbiology, 2018)
Summary Diatoms are a highly successful group of photosynthetic protists that often thrive under adverse environmental conditions. Members of the genus Pseudo‐nitzschia are ecologically important diatoms which are able to subsist during periods of chronic iron limitation and form dense blooms following iron fertilization events. The cellular strategies within diatoms that orchestrate these physiological responses to variable iron concentrations remain largely uncharacterized. Using a combined transcriptomic and proteomic approach, we explore the exceptional ability of a diatom isolated from the iron‐limited Northeast Pacific Ocean to reorganize its intracellular processes as a function of iron. We compared the molecular responses of Pseudo‐nitzschia granii observed under iron‐replete and iron‐limited growth conditions to those of other model diatoms. Iron‐coordinated molecular responses demonstrated some agreement between gene expression and protein abundance, including iron‐starvation‐induced‐proteins, a putative iron transport system and components of photosynthesis and the Calvin cycle. Pseudo‐nitzschia granii distinctly differentially expresses genes encoding proteins involved in iron‐independent photosynthetic electron transport, urea acquisition and vitamin synthesis. We show that P. granii is unique among studied diatoms in its physiology stemming from distinct cellular responses, which may underlie its ability to subsist in low iron regions and rapidly bloom to outcompete other diatom taxa following iron enrichment.

Divergent gene expression among phytoplankton taxa in response to upwelling - Robert H. Lampe; Natalie R. Cohen; Kelsey A. Ellis; Kenneth W. Bruland; Maria T. Maldonado; Tawnya D. Peterson; Claire P. Till; Mark A. Brzezinski; Sibel Bargu; Kimberlee Thamatrakoln; Fedor I Kuzminov; Benjamin S. Twining; et al. (Environmental Microbiology, 2018)
Summary Frequent blooms of phytoplankton occur in coastal upwelling zones creating hotspots of biological productivity in the ocean. As cold, nutrient‐rich water is brought up to sunlit layers from depth, phytoplankton are also transported upwards to seed surface blooms that are often dominated by diatoms. The physiological response of phytoplankton to this process, commonly referred to as shift‐up, is characterized by increases in nitrate assimilation and rapid growth rates. To examine the molecular underpinnings behind this phenomenon, metatranscriptomics was applied to a simulated upwelling experiment using natural phytoplankton communities from the California Upwelling Zone. An increase in diatom growth following 5 days of incubation was attributed to the genera Chaetoceros and Pseudo‐nitzschia . Here, we show that certain bloom‐forming diatoms exhibit a distinct transcriptional response that coordinates shift‐up where diatoms exhibited the greatest transcriptional change following upwelling; however, comparison of co‐expressed genes exposed overrepresentation of distinct sets within each of the dominant phytoplankton groups. The analysis revealed that diatoms frontload genes involved in nitrogen assimilation likely in order to outcompete other groups for available nitrogen during upwelling events. We speculate that the evolutionary success of diatoms may be due, in part, to this proactive response to frequently encountered changes in their environment.

Iron storage capacities and associated ferritin gene expression among marine diatoms - Natalie R. Cohen; Elizabeth Mann; Brooke Stemple; Carly M. Moreno; Sara Rauschenberg; Jeremy E. Jacquot; William G. Sunda; Benjamin S. Twining; Adrian Marchetti (Limnology and Oceanography, 2018)
In large regions of the ocean, low iron availability regulates diatom growth and species composition. Diatom species often vary in their physiological response to iron enrichment, with natural and artificial iron additions in iron‐limited regions of the ocean resulting in large blooms of primarily pennate diatoms. The ability of pennate diatoms to proliferate following pulse iron additions has been partly attributed to their ability to acquire and store excess intracellular iron in the iron storage protein ferritin. Recent transcriptome sequencing of diatoms indicate that some centric diatoms also possess ferritin. Using a combination of physiological and molecular techniques, we examined the iron storage capacities and associated ferritin gene expression in phylogenetically diverse centric and pennate diatoms grown under high and low iron concentrations. There were no systematic differences among ferritin‐containing and non‐containing diatom lineages in their ability to store iron in excess of that needed to support maximum growth rates. An exception, however, was the ferritin‐containing pennate diatom Pseudo‐nitzschia granii , native to iron‐limited waters of the Northeast Pacific Ocean. This species exhibited an exceptionally large luxury iron storage capacity and increased ferritin gene expression at high iron concentrations, supporting a role in long‐term iron storage. By contrast, two other diatoms species that exhibited minimal iron storage capacities contained two distinct ferritin genes where one ferritin gene increased in expression under iron limitation while the second showed no variation with cellular iron status. We conclude that ferritin may serve multiple functional roles that are independent of diatom phylogeny.

Symbiodinium Functional Diversity in the Coral Siderastrea siderea Is Influenced by Thermal Stress and Reef Environment, but Not Ocean Acidification - Sarah W. Davies; Justin B. Ries; Adrian Marchetti; Karl D. Castillo (Frontiers in Marine Science, 2018)

Corrigendum: Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2018)

Examination of gene repertoires and physiological responses to iron and light limitation in Southern Ocean diatoms - Carly M. Moreno; Yajuan Lin; Sarah Davies; Elaine Monbureau; Nicolas Cassar; Adrian Marchetti (Polar Biology, 2018)

Eukaryotic phytoplankton community spatiotemporal dynamics as identified through gene expression within a eutrophic estuary - Weida Gong; Hans Paerl; Adrian Marchetti (Environmental Microbiology, 2018)
Summary Over the span of a year, we investigated the interactions between biotic and abiotic factors within the eutrophic Neuse River Estuary (NRE). Through metatranscriptomic sequencing in combination with water quality measurements, we show that there are different metabolic strategies deployed along the NRE. In the upper estuary, taxonomically resolved phytoplankton groups express more transcripts of genes for synthesis of cellular components and carbon metabolism whereas in the lower estuary, transcripts allocated to nutrient metabolism and transport were more highly expressed. Metabolisms for polysaccharide synthesis and transportation were elevated in the lower estuary and could be reflective of unbalanced growth and/or interactions with their surrounding microbial consortia. Our results indicate phytoplankton have high metabolic activity, suggestive of increased growth rates in the upper estuary and display patterns reflective of nutrient limitation in the lower estuary. Among all the environmental parameters varying along the NRE, nitrogen availability is found to be the main driving factor for the observed spatial divergence.

Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2017)
Changes in iron (Fe) bioavailability influence diatom physiology and community composition, and thus have a profound impact on primary productivity and ecosystem dynamics. Iron limitation of diatom growth rates has been demonstrated in both oceanic and coastal waters of the Northeast Pacific Ocean and is predicted to become more pervasive in future oceans. However, it is unclear how the strategies utilized by phytoplankton to cope with low Fe bioavailability and resupply differ across these ocean provinces. We investigated the response of diatom communities to variable Fe conditions through incubation experiments performed in the Fe mosaic of the California Upwelling Zone and along a natural Fe gradient in the Northeast Pacific Ocean. Through coupling gene expression of two dominant diatom taxa ( Pseudo-nitzschia and Thalassiosira ) with biological rate process measurements, we provide an in-depth examination of the physiological and molecular responses associated with varying Fe status. Following Fe enrichment, oceanic diatoms showed distinct differential expression of gene products involved in nitrogen assimilation, photosynthetic carbon fixation, and vitamin production compared to diatoms from low-Fe coastal sites, possibly driven by the chronic nature of Fe stress at the oceanic site. Genes of interest involved in Fe and N metabolism additionally exhibited divergent expression patterns between the two diatom taxa investigated, demonstrating that diverse diatoms may invoke alternative strategies when dealing with identical changes in their environment. We report here several mechanisms used distinctly by coastal or oceanic diatom communities as well as numerous taxa-specific strategies for coping with Fe stress and rearranging nutrient metabolism following Fe enrichment.

Iron and vitamin interactions in marine diatom isolates and natural assemblages of the Northeast Pacific Ocean - Natalie R. Cohen; Kelsey A. Ellis; Wilton G. Burns; Robert H. Lampe; Nina Schuback; Zackary Johnson; Sergio Sañudo‐Wilhelmy; Adrian Marchetti (Limnology and Oceanography, 2017)
Trace metals and B‐vitamins play critical roles in regulating marine phytoplankton growth and composition. While some microorganisms are capable of producing certain B‐vitamins, others cannot synthesize them and depend on an exogenous supply. Therefore, external factors influencing vitamin synthesis, such as micronutrient concentrations, alter the extent to which B‐vitamins are available to auxotrophs in surface waters. We examined iron, B 7 (biotin) and B 12 (cobalamin) dynamics in diatoms through laboratory culture experiments and within natural diatom assemblages present along an iron gradient in the Northeast Pacific Ocean. In laboratory cultures of the diatom Pseudo‐nitzschia granii , biotin synthase (BIOB ) expression decreased 2‐fold under iron limitation, suggesting iron status may affect B 7 production in diatoms. Additionally in laboratory cultures of the diatom Grammonema cf. islandica , which contains a B 12 ‐independent methionine synthase ( METE ), a 15‐fold increase in the expression of METE was observed when grown in the absence of B 12 with no significant influence of iron status, suggesting METE expression can be driven by B 12 status alone. Iron and B‐vitamin amendment experiments with natural diatom assemblages in iron‐limited waters of the Northeast Pacific Ocean provide evidence for vitamin‐associated molecular responses that suggest elevated B 7 biosynthesis and the emergence of B 12 limitation following iron addition. Furthermore B‐vitamin gene modules comprised of partial and/or complete B‐vitamin biosynthetic pathways in diatoms increased in response to iron addition, including genes potentially involved in the processing of B 12 intermediates. Our results indicate that vitamins may play an important role in regulating phytoplankton growth and composition in this region, particularly following natural iron addition events.

Thermal and pCO2 Stress Elicit Divergent Transcriptomic Responses in a Resilient Coral - Sarah W. Davies; Adrian Marchetti; Justin B. Ries; Karl D. Castillo (Frontiers in Marine Science, 2016)

Frustule‐related gene transcription and the influence of diatom community composition on silica precipitation in an iron‐limited environment - Colleen A. Durkin; Adrian Marchetti; Sara J. Bender; Tiffany Truong; Rhonda Morales; Thomas Mock; E. Virginia Armbrust (Limnology and Oceanography, 2012)
A microcosm study in iron‐limited waters of the northeast subarctic Pacific Ocean was conducted to examine how iron availability affects the frustule‐related response of individual diatoms and thus the total quantity of silica precipitated by the community. New silica precipitated per cell was estimated using the fluorescent cell stain 2‐(4‐pyridyl)‐5{[4‐dimethylaminoethyl‐aminocarbamoyl)‐methoxy]phenyl}oxazole (PDMPO). Differences in new silica precipitation within a particular genus before and after iron enrichment were small compared to differences among genera, indicating that the quantity of total silica precipitated is particularly sensitive to community composition. Transcriptional patterns of genes encoding silicon transporters, aminopropyltransferases, chitin synthases, and a protein with uncharacterized function were measured in natural populations to identify indicators of the frustule‐related responses of different genera to iron limitation. Transcripts associated with silicon transporters were the most readily detectable in three metatranscriptome datasets and were capable of resolving species composition shifts and physiological responses. Silicon transporter transcripts from a distinct phylogenetic clade were most abundant in the iron‐limited community, and transcripts from a separate clade were more abundant in the community that bloomed after iron enrichment. Transcripts of the gene present in the iron‐limited community were also more abundant in iron‐limited laboratory cultures of Pseudo‐nitzschia multiseries , suggesting that this gene plays a role in silicon uptake during iron limitation. The responses of individual cells, as detected in this study, determine how the community influences silicon cycling in iron‐limited environments.

Iron and silicic acid effects on phytoplankton productivity, diversity, and chemical composition in the central equatorial Pacific Ocean - Adrian Marchetti; Diana E. Varela; Veronica P. Lance; Veronica P. Lance; Matteo Palmucci; Mario Giordano; E. Virginia Armbrust (Limnology and Oceanography, 2010)
A microcosm nutrient‐amendment experiment using central equatorial Pacific Ocean (0°, 140°W) mixed‐layer waters was conducted to determine biogeochemical controls on phytoplankton with an emphasis on post‐iron enrichment nutrient uptake dynamics and species composition. The addition of either Fe (termed Fe‐only) or Fe and Si(OH) 4 (termed FeSi) to on‐deck incubations resulted in growth primarily of pennate diatoms, with statistically equivalent increases relative to the control in maximum photochemical efficiency, chlorophyll a (Chl a ) concentrations, particulate organic carbon and nitrogen concentrations, and dissolved inorganic carbon uptake rates. In contrast, at peak Chl a concentrations, there was a 3.4‐fold higher abundance of large diatoms and a 3.9‐ fold lower abundance of small pennate diatoms in FeSi relative to Fe‐only, which translated into a 3.5‐fold higher Si(OH) 4 uptake rate and a 2.1‐fold higher biogenic silica concentration. Fourier transform infrared spectroscopy indicated that relative to cells from Fe‐only, cells from FeSi possessed the lowest protein : carbohydrate ratios, and ratios of lipids, proteins, and carbohydrates relative to silica, consistent with differences in diatom C allocation or increased silicification or both. Our results suggest that after Fe addition, diatom organic matter accumulation rates (i.e., C and N uptake rates) are enhanced but the low, ambient [Si(OH) 4 ] retards cell division rates, resulting in fewer large diatoms with relatively high C and N contents. After the simultaneous addition of Fe and Si(OH) 4 , enhanced rates of diatom organic matter accumulation and cell division results in more large, heavily silicified diatoms with relatively low C and N contents.

Coupled changes in the cell morphology and elemental (C, N, and Si) composition of the pennate diatom Pseudo‐nitzschia due to iron deficiency - Adrian Marchetti; Paul J. Harrison (Limnology and Oceanography, 2007)
We investigated the changes in cell morphology and elemental composition with varying iron nutritional status in four oceanic and two coastal isolates of the marine pennate diatom Pseudo‐nitzschia . When iron‐deficient, most isolates exhibited slower specific growth rates (m), reduced maximum photochemical yields (WM), and lower chlorophyll a (Chl a ) contents than iron‐replete cultures. Iron‐deficient cells exhibited reduced cell volumes, primarily as the result of decreased valve transapical widths, which increased the valve aspect ratios. The increase in aspect ratios varied among isolates and was not correlated with the degree of growth limitation due to irondeficiency. In all Pseudo‐nitzschia isolates, the mean carbon (C cell ), nitrogen (N cell ), and silicon (Si cell ) cell quotas of iron‐deficient cells decreased when compared to iron‐replete cells. Similarly, in five out of the six isolates, the mean C and N quotas normalized per unit cell volume (C vol and N vol ) of iron‐deficient cells also decreased, but by a lesser extent. In contrast, there were no clear differences in the changes in the mean Si quotas normalized per unit cell surface area (Si sa ). The Si cell :N cell and Si cell : C cell ratios (quotas normalized per cell) of iron‐deficient cells increased compared to iron‐replete conditions due to greater reductions in C and N cell quotas compared to Si cell quotas. This increase in the Si cell :N cell ratio was proportional to the changes in the valve aspect ratios. Our results show that iron‐deficient Pseudo‐nitzschia cells acclimate to low iron concentrations by increasing their valve aspect ratios, thus reducing their cell volumes and increasing their surface area‐to‐volume (SA : V) ratios. These changes in cell morphology increase the Si‐containing valve surface area relative to the volume of the internal components, which may then influence the cellular elemental composition, in particular, the Si :N and Si :C ratios.